Принципи добору асортименту деревно-кущових рослин для стеблової репродукції на південному сході України - Glukhov, О.Z.; Dovbysh, N.F.; Kharkhota, L.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2010)
Generalized principles of selecting an assortment of species and cultivars of ornamental deciduous shrubs for propagating by stem cutting in order to introduce them into greenery planting in the southeast of Ukraine are elaborated.